2006
DOI: 10.1111/j.1574-6968.2006.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of cell division and cell wall synthesis genes reveals mutationally inactivatedftsQandmraYin a protoplast-type L-form ofEscherichia coli

Abstract: Cell division and cell wall synthesis are tightly linked cellular processes for bacterial growth. A protoplast-type L-form Escherichia coli, strain LW1655F+, indicated that bacteria can divide without assembling a cell wall. However, the molecular basis of its phenotype remained unknown. To establish a first phenotype-genotype correlation, we analyzed its dcw locus, and other genes involved in division of E. coli. The analysis revealed defective ftsQ and mraY genes, truncated by a nonsense and a frame-shift mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 24 publications
3
28
0
Order By: Relevance
“…In bacterial L-forms, which lack a cell wall, it might be supposed that the requirement for many of the dcw genes would be reduced and less transertion would occur. This would be consistent with the findings that, in L-forms of E. coli , some of the genes were mutated (Siddiqui et al, 2006) and the levels of FtsZ were fivefold lower (Onoda et al, 2000) whilst in an L-form of B. subtilis FtsZ could be eliminated altogether (Leaver et al, 2009). …”
Section: Hyperstructuressupporting
confidence: 89%
“…In bacterial L-forms, which lack a cell wall, it might be supposed that the requirement for many of the dcw genes would be reduced and less transertion would occur. This would be consistent with the findings that, in L-forms of E. coli , some of the genes were mutated (Siddiqui et al, 2006) and the levels of FtsZ were fivefold lower (Onoda et al, 2000) whilst in an L-form of B. subtilis FtsZ could be eliminated altogether (Leaver et al, 2009). …”
Section: Hyperstructuressupporting
confidence: 89%
“…Despite numerous studies, little is known about the mechanisms of L-form formation. Previous studies have mainly identified mutations in genes involved in cell wall synthesis or cell division in stable L-form bacteria being important for L-form formation [6], [9], [10], [11]. Using E. coli unstable L-form bacteria as a model, we recently systematically examined the molecular basis of L-form formation by microarray analysis and mutant screens and identified a network of genes and pathways involved in L-form formation or survival [7].…”
Section: Introductionmentioning
confidence: 99%
“…The L -forms may assume a transient state (that is, reversion to the walled form is possible), or a stable state, in which they can be cultivated in absence of the inducing agent (without reversion). Several mutations were reported to support L -form conversion345, and it was also shown that deleterious mutations may accumulate during the L -form state, possibly preventing subsequent regeneration of a mature cell wall6.…”
mentioning
confidence: 99%